Analysing the factors affecting the purchasing decision over Malaysian batik products - Simin, Ummihabibah; Abd Rahman, Nur Hidayah (2020)
Malaysian batik is a highly purchased handicraft in comparison to other handicraft products. There has been a scarcity of previous studies in addressing the factors affecting the purchasing decision over the traditional textile, which is batik. Hence, this study aims to analyse the factors that affect the purchasing decision over Malaysian batik products. This study has employed quantitative research by distributing questionnaires consisting of 35 questions, which were categorized into four sections. This study also employed the purposive sampling technique with a total of 62 respondents who completed the questionnaires. The study found that six factors affect the purchasing decision over Malaysian batik products, which are: the quality factor, price factor, availability factor, packaging factor, reference factor, and brand factor. Besides, other factors have been identified from the open-ended question, namely the promotion and awareness, design and color, identity and authenticity, and usability. The study suggested exploring the promotion and awareness factor, design and color factor, identity and authenticity factor, and usability factor that affect the purchasing decisions over Malaysian batik products. The findings of the study would benefit the batik industry by enhancing the use of Malaysian batik and increasing the sales value of Malaysian batik.